Implementation of a clinical decision rule for selecting empiric treatment for invasive aspergillosis in a setting with high triazole resistance. (23rd November 2021) - van de Peppel, Robert J; van Grootveld, Rebecca; Hendriks, Bart J C; van Paassen, Judith; Bernards, Sandra; Jolink, Hetty; Koopmans, Julia G; von dem Borne, Peter A; van der Beek, Martha T; de Boer, Mark G J
Abstract: World-wide, emerging triazole resistance increasingly complicates treatment of invasive aspergillosis (IA). In settings with substantial (>10%) prevalence of triazole resistance, empiric combination therapy with both a triazole and liposomal amphotericin B (LAmB) can be considered because of the low yields of susceptibility testing. To avoid toxicity while optimizing outcome, a strategy with monotherapy would be preferable. A newly designed treatment algorithm based on literature and expert consensus provided guidance for empiric monotherapy with either voriconazole or LAmB. Over a four and a half year period, all adult patients in our hospital treated for IA were included and patient data were collected. An independent committee reviewed the attributability of death to IA for each patient. Primary outcomes were 30- and 100-day crude mortality and attributable mortality. In total, 110 patients were treated according to the treatment algorithm. Fifty-six patients (51%) were initially treated with voriconazole and 54 patients (49%) with LAmB. Combined attributable and contributable mortality was 13% within 30 days and 20% within 100 days. Treatment switch to LAmB was made in 24/56 (43%) of patients who were initially treated with voriconazole. Combined contributable and attributable 100-day mortality in this subgroup was 21% and was not increased when compared with patients initially treated with LAmB ( P = 0.38). By applying a comprehensive clinical decision algorithm, an antifungal-sparing regime was successfully introduced. Further research is warranted to explore antifungal treatment strategies that account for triazole-resistance. Lay summary: Due to resistance of Aspergillus against triazoles, combination therapy with liposomal amphotericin B (LAmB) is applied more often as primary therapy against invasive aspergillosis. This study presents the results of a decision tool which differentiated between triazole or LAmB monotherapy.